Re-sampling of continuous scanning LDV data for ODS extraction. (May 2016) - Castellini, P.; Sopranzetti, F.; Martarelli, M.
Abstract: The paper presents a method for processing data obtained by Continuous Scanning Laser Doppler Vibrometry (CSLDV) that makes it possible to measure vibrations combining spatial and temporal information. Since the laser continuously scans the structure under test over time and space, it measures a vibration signal modulated by the Operational Deflection Shape (ODS) of the structure. CSLDV time history can then be re–sampled at an arbitrary spatial resolution in order to recover the vibration data at several positions on the trajectory swept by the laser. The main drawback of such method is that the actual sampling rate of the re–sampled vibration signals is dictated by frequencies of the mirrors, which determine the laser scanning speed. The paper presents a method for the automatic recognition of "aliased" natural frequencies and recovery of the actual un–aliased natural frequencies. Once those frequencies are determined, the corresponding ODSs are recovered. Abstract : Highlights: The paper illustrates a re-sampling method for processing CSLDV data. CSLDV acquires simultaneously spatial and time information. CSLDV signals can be re-sampled with high spatial resolution, but aliasing occurs. The automatic recognition of "aliased" natural frequencies is presented. The automatic recovery of the actual un-aliased natural frequencies is presented. The ODS phase correction is done to take into account the un-synchronous acquisition.